2023
DOI: 10.3389/feart.2023.1183150
|View full text |Cite
|
Sign up to set email alerts
|

An efficient spectral element method for two-dimensional magnetotelluric modeling

Abstract: We introduce a new efficient spectral element approach to solve the two-dimensional magnetotelluric forward problem based on Gauss–Lobatto–Legendre polynomials. It combines the high accuracy of the spectral technique and the perfect flexibility of the finite element approach, which can significantly improve the calculation accuracy. This method mainly includes two steps: 1) transforming the boundary value problem in the partial differential form into the variational problem in the integral form and 2) solving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 64 publications
0
0
0
Order By: Relevance
“…The computational modeling partial differential equation (PDE) has demonstrated that the spectral-element method possesses more appealing characteristics compared to the traditional FDM and FEM. As a high-order finite-element approach, the spectral-element method can combine the complex geometric flexibility of the FEM with the high accuracy of the spectral method [19,20]. The finite-element method enables the simulation of complex real-world information, including topography and bathymetry, while enhancing the flexibility of discretization domains in 2D and 3D conductivity models.…”
Section: Introductionmentioning
confidence: 99%
“…The computational modeling partial differential equation (PDE) has demonstrated that the spectral-element method possesses more appealing characteristics compared to the traditional FDM and FEM. As a high-order finite-element approach, the spectral-element method can combine the complex geometric flexibility of the FEM with the high accuracy of the spectral method [19,20]. The finite-element method enables the simulation of complex real-world information, including topography and bathymetry, while enhancing the flexibility of discretization domains in 2D and 3D conductivity models.…”
Section: Introductionmentioning
confidence: 99%